0296 The NIEHS GuLF STUDY: Correlations of Concentrations Between Various Oil Chemicals and Total Hydrocarbons. (23rd June 2014) - Groth, Caroline; Banerjee, Sudipto; Huynh, Tran; Ramachandran, Gurumurthy; Stenzel, Mark; Stewart, Patricia; Blair, Aaron; Engel, Lawrence; Sandler, Dale; Kwok, Richard
Abstract : Objectives: In the 2010 Deepwater Horizon Oil Spill, thousands of workers may have been exposed to various potentially harmful chemicals found in crude oil including benzene, ethylbenzene, xylene, and toluene. These and total hydrocarbons (THC) (a composite of all the volatile chemicals in crude oil) were monitored. Over 150 000 personal measurements were taken, but many of the measurements of individual chemicals were below the analytic method's limit of detection (LOD), making estimation of exposure levels challenging. The concentration of each chemical relative to THC is related to the concentration of the chemical and THC in the source crude oil. Knowing these relationships, we can develop models to predict concentrations of individual chemicals from THC concentrations when only a THC concentration was detectable. The goal of this study was to determine the correlations between concentrations of the various oil chemicals and THC for use in situations where only THC was above the LOD. Method: We calculated correlations on the rig ships and support vessels located near the well by vessel and time period using linear regression analysis that accounts for censored data. Results: We found significant differences in correlations between concentrations of the chemicals and THC across vessels and over time that likely reflect different vessel activities and degrees of crude oil weathering throughout the response and clean-up efforts. Conclusions: Correlations between concentrations of the chemicals of interest and THC can be used to estimate the chemical's concentration when its measurement is below the LOD.